An S-scheme NH2-UiO-66/SiC photocatalyst via microwave synthesis with improved CO2 reduction activity. (January 2022) - Xiao, Shuning; Guan, Yuchuan; Shang, Huan; Li, Haoliang; Tian, Zhangliu; Liu, Suya; Chen, Wei; Yang, Junhe
Highlights: An S-scheme composite catalyst NH2 -UiO-66/SiC synthesized by microwave. Microwave super-hot dots on SiC provides a strongly bonded interface. Porous structure of NH2 -UIO-66 enables effective CO2 adsorption. Interfacial coupling facilitated the efficient separation of photogenerated carriers. S-Scheme charge transfer inhibited recombination of electron-holes. Abstract: High CO2 adsorption capacity and rapid photo-generated carrier separation are the keys to raising artificial photosynthesis efficiency. Herein, an NH2 -UiO66/SiC composite photocatalyst was synthesized by microwave based on the super-hot spot heating mechanism on SiC. The composite reached a CO production of 7.30 μmol g −1 h −1 in gas-solid phase CO2 reduction reaction, which was over 5 times higher than that of NH2 -UiO-66. The improved photocatalytic activity can be attributed to the unique physical and chemical structures of the catalyst, including: (1) high specific surface area enhances the adsorption capacity of CO2 molecules, (2) in-situ microwave synthesis provides the chemical bonded interfaces towards a faster carrier transfer kinetic, (3) constructed S-scheme heterojunction accelerates the separation of photogenerated carriers and improves the utilization of electron. This work creates new insights into the synthesis of composite nanomaterials based on microwave absorbing materials as well as the design of S-scheme photocatalysts.